KINERJA BIAYA DAN WAKTU PROYEK DENGAN METODE EARNED VALUE MANAGEMENT - I Gede Ngurah Sunatha; Anak Agung Ratu Ritaka Wangsa; Tjokorda Istri Praganingrum; Putu Mia Loviani (Fakultas Sains dan Teknologi Universitas Ngurah Rai, 2023)
cost and time planning and control are part of overall construction project management. The cost and time used in completing a job are continuously measured against the plan. Significant deviations in cost and time indicate poor project management. In the implementation of the construction project for the Dean's Office of the Faculty of Medicine at Udayana University, a delay of 34.15% in project realization progress was observed in the 13th week, while the planned progress was 38.14% in the 13th week. Earned Value Management (EVM) is a control method used to manage project costs and schedules in an integrated manner. This method provides information on project performance in terms of cost and time for a reporting period and provides projections of the costs and time required to complete the project. The results of the analysis show the values for Actual Cost Work Performed (ACWP) as Rp. 13,522,731,641, Budgeted Cost of Work Schedule (BCWS) as Rp. 9,224,298,540, and Budgeted Cost Work Performance (BCWP) as Rp. 8,260,099,464. The average CPI value of 1.30>1 indicates that the project performance is better than planned, while the average SPI value of 0.99<1 means that the project is running behind the scheduled plan. The analysis results for the project completion projections are as follows: Estimate Temporary Cost (ETC) is Rp. 12,223,343,210, Estimate All Cost (EAC) is Rp. 25,746,074,851, Estimate Temporary Schedule (ETS) is 48 days, and Estimate All Schedule (EAS) is 139 days.